PERWUJUDAN SISTEM TATA PEMERINTAHAN YANG BAIK MELALUI SINERGI DAN KOLABORASI ANTARA POLITIK DAN BIROKRASI DI INDONESIA - Kurhayadi (Jurnal Kelola: Jurnal Ilmu Sosial, 2020)
This research will be carried out with the aim of being able to see how good governance can be realized by means of a mutually supportive synergy between politics and the bureaucracy. This research will look at various factors that occur and can influence the relationship between politics and the bureaucracy so that good governance can be created. A qualitative approach will be used in this study as a research method. The data used in the study came from various journal articles which are considered to still have relevance to this research. The results of this study found that good governance requires a collaboration that goes well between politics and the bureaucracy. There are several factors that have a role in the relationship that occurs between politics and the bureaucracy, namely power, human resources and the recruitment system. So that there is no superiority between these two things, politics and bureaucracy need to be placed on the same position. It is through the balance between these two things that good governance can be realized to the fullest.